COMMENT FROM CHIEF WILLIAM STAMM MILWAUKEE FIRE DEPARTMENT FOR FIRE SAFE CIGARETTE TECHNICAL STUDY GROUP MEETING 850711 - F,E; STAMM,W (Tufts Archival Research Center, 2007)
For Filing; Handwritten; Illegible/Difficult to Read; Comments from the Fire Chief of the Milwaukee Fire Department regarding the fire safe cigarette study group meeting. Mentions that the Chief will present the findings of the study group and expresses concern about obtaining scientific findings without political bias.